Whiffs of waste: product application preferences among Saudis and Malaysians for material from coffee ground waste - Ismail, Zati Hazira; Bahrudin, Fadzli Irwan; Daud, Nuraini; Liew, Yong Kian; Hamat, Basyarah (Springer, 2025)
In industrial design, sustainably focused materials, such as recyclable and renewable materials, are rapidly emerging. Product materials are linked to their origins when narrating their claims in sustainable marketing. Coffee ground waste is now used in non-food items like cups and eyewear. Online users connect material information to their knowledge of its origin, influenced by product types and cultural backgrounds. The Implicit Association Test (IAT) tested positive and negative associations of coffee ground waste materials with various products among respondents from Saudi Arabia and Malaysia. Malaysian respondents associated the material with food-related products and “indulgent”, while Saudi respondents linked it to memorabilia and “sentimental”. This study’s findings provided valuable insights for designers, enabling them to strategically apply materials made from Coffee Ground Waste to ensure a positive reception in the market.